Kinetic Sorption Studies of Heavy Metal Contamination on Indian Expansive Soil - M. K. Gupta; A. K. Singh; R. K. Srivastava (E-Journal of Chemistry)
Sorption of metallic cadmium from the pH adjusted aqueous solutions at varying initial concentrations onto an alluvial (clay) soil through batch sorption experiments was studied. The pH of the initial concentrations ranging between 50 mg/L to 250 mg/L was varied from 3.0 to 8.0. The sorption experiments were carried out for different durations and up to 16 hours. The cadmium continued to sorb till the last experimental pH=8. The experimental sorption data fitted very well with both Langmuir and Freundlich isotherm models and Freundlich model gave higher correlation coefficients. The pseudo-second order kinetics model was most agreeable with the experimental sorption data, whereas the pseudo-first order model was found to be insufficient.